Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 13831 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Crassiclitellata", "Geometry POLYGON((-180 -82,-180 82,180 82,180 -82,-180 -82))", "HasGeospatialIssue is false", "BasisOfRecord is Specimen" ] } The dataset includes 13831 records from 24 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003890-150316153013904/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences